Identification of fructans in Agave fourcroydes (henequ?n) as source of additive in animal production in Cuba - Garc?a Curbelo, Yanelys; L?pez, Mercedes G.; Bocourt, Ram?n (Cuban Journal of Agricultural Science, 2013)
The presence of fructans was determined in Agave fourcroydes in Cuba through the use of infrared spectroscopy with Fourier transformation in the mid-infrared area. Lyophilized samples of carbohydrates extracted from stems and leaves of Agave fourcroydes were used. In all instances, there was identification of fructans. In the infrared spectra, there were bands of strong absorption at 3400-3200 cm-1, typical of OH bonds, as well as bands of absorption of carbon groups at 1900-1580 cm-1, bonds between ?C-O-C- monomers at 1150-1050 cm-1, cyclic alcohol at 1065-1015 cm-1 and C-O-C, due to the presence of oxygen in asymmetric rings at 950-890 cm-1. The elucidation of these molecular structures is of great relevance in the future work developed in Cuba with these crops, specifically to assess the physiological function in the plant and as source of obtainment of prebiotic products. Key words: fructans, Agave fourcroydes, infrared spectroscopy.